The Influence of Differentiated Learning Style Strategies on Reading Skills - Hamdah, Ninda Miftahul; Jumhana, Nana; Irma, Ade (Proceeding of Annual International Conference on Islamic Education and Language (AICIEL), 2025)
This research was conducted to address problems in the instruction of reading skills (mahārah qirā’ah) that ultimately contribute to low student interest and motivation. The general objective of this study is to accommodate differences in students' ability to absorb learning material, thereby helping students increase their learning motivation. More specifically, the research focuses on the specification of differentiated teaching strategies tailored to students' learning styles, integrated with appropriate teaching methods and media. This approach not only clarifies the focus on reading skills but also assists teachers in selecting suitable instructional media, making the method more applicable in the context of Arabic language learning. This research addresses the gap in the aspect of concrete strategy based on learning styles and the utilization of appropriate media, while simultaneously providing a quantitative measurement of the method's effectiveness. This study also offers a new perspective on mahārah qirā’ah instruction within the context of the Kurikulum Merdeka (Independent Curriculum). The methodology employed in this study is a qualitative method with a quasi-experimental design. The results of the pre-test and post-test show a significant increase in the experimental class that used the differentiated teaching strategy. The average pre-test score in the experimental class was 54.90, which increased to 86.35 on the post-test. The control class also showed an increase, from 45.45 to 59.42. However, all students in the experimental class experienced an increase in scores, while some scores in the control class remained unchanged or decreased.